Incorporation of Molybdate Anion into -FeOOH - Carroll, Dale; Richmond, William (Mineralogical Society of America, 2008)
An analogue of -FeOOH (akaganite) containing structurally-incorporated molybdate has beensynthesized and the conditions for its formation have been studied in the presence of chloride, sulfateand nitrate anions. The incorporation of molybdate into the -FeOOH structure has been shown togreatly increase the stability of this phase with respect to its transformation to hematite at elevatedtemperature. Molybdate incorporation has also been shown to change the particle morphology, withincreasing amounts of molybdate causing the rod-shaped nanoparticles to become progressively shorteruntil spherical nanocrystals are observed. The combined observations of increased stability, morphologychanges and measured levels of incorporated molybdenum suggest that although inclusion of molybdateanions into the -FeOOH tunnel sites is possible, it is unlikely to be the only mode of molybdateincorporation.